Diagnóstico e tratamento da dor neuropática em pacientes tratados de hanseníase - Del’Arco, Rogério (2014)
Introduction. Chronic pain in leprosy plays an important role for being responsible for the physical and psychological suffering that produces. Objectives: To identify the difficulties in diagnosing and treating neuropathic pain caused by Leprosy, as well as to investigate the main determinants of neuropathic pain. Methods: Eighty-five patients who completed treatment for leprosy with MDT/WHO were evaluated for neuropathic pain using the Douleur Neuropathic 4 test (DN4). A detailed questionnaire and neurological examination were employed to complement the results. Results: Forty-eight patients were excluded because they did not have pain at the time of this study. Of the 37 patients with pain, 22 (59.5%) reported neuropathic or mixed pain and 70.8% characterized their pain as moderate or severe; 81.8% had suffered with pain for more than 6 months. Only 12 (54.5%) patients had been diagnosed with the symptom and so the problem had not been identified in almost half of the cases (10; 45.5%). Of the 12 patients on medications for neuropathic pain, only 5 (41.6%) stated that it had improved with the pain of the other 7 patients (58.4%) remaining the same or getting worse. The difference in the improvement of pain between treated (n = 12) and untreated patients (n = 10) was significant (p-value = 0.020). Conclusion: Neuropathic pain is an important cause of suffering for patients with leprosy and is still neglected by the medical team because of difficulties to diagnose it. The appropriate recognition and treatment of this condition may relieve symptoms and improve the quality of life of patients.